Perinatal exposure to endocrine disruptors: sex, timing and behavioral endpoints. (February 2016) - Palanza, Paola; Nagel, Susan C; Parmigiani, Stefano; vom Saal, Frederick S
Highlights: EDCs alter behavior in a sex, time and exposure dependent manner. Perinatal BPA exposure eliminates many sex differences in behavior in rodents. Endocrine disrupting chemicals (EDCs) interfere with brain sexual differentiation. Sexually dimorphic behaviors are sensitive endpoints of developmental EDC exposure. Abstract : Of the approximately 85, 000 chemicals in use, 1000 have been identified as having the ability to disrupt normal endocrine function. Exposure to endocrine disrupting chemicals (EDCs) during critical period in brain differentiation (prenatal and neonatal life) via the mother can alter the course of the development of sexually dimorphic behaviors. Bisphenol A (BPA) is a very high volume chemical used in plastic, resins and other products, and virtually everyone examined has detectable BPA. BPA has estrogenic activity and is one of the most studied EDCs. We review evidence from studies in rodents using dose levels relevant to human exposure. BPA alters behavior and eliminates or in some cases reverses sexually dimorphic behaviors observed in unexposed animals.